MANAJEMEN JASA PENDIDIKAN DALAM MENINGKATKAN KUALITAS PELAYANAN PESERTA DIDIK DI SMP TARBIYATUL UMMAH KOTA TASIKMALAYA - Sa’diah Charmila; Hardi Humaedi Hidayat; Tsani Tsamrotul Fuadah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the quality of services provided to students and to identify various obstacles encountered in school service management in 2025. In addition, this research examines strategies to overcome challenges in educational service management in order to improve the quality of student services at SMP Tarbiyatul Ummah Cibunigeulis Bungursari, Tasikmalaya City. This study employs a qualitative approach with a case study design. The findings indicate that the school’s commitment to providing affordable and high-quality education is reflected in various programs, such as free education, religious activities, extracurricular programs, and financial assistance for students in need. However, the school still faces several challenges, including limited funding, incomplete facilities and infrastructure (such as science laboratories, language laboratories, sports facilities, and traditional arts equipment), as well as issues related to students’ motivation, discipline, and participation. This study specifically highlights the management of educational services in improving the quality of student services during the 2025–2026 period by considering existing limitations. The findings provide a comprehensive and naturalistic understanding of the phenomenon of educational service management and offer practical implications for enhancing student satisfaction and overall educational quality in similar institutional settings.